Perancangan Sistem Informasi Pendistribusian Baja Ringan Pada PD. Karunia - Widiani, Elvira; Amroni; Mery (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2023)
PD. Karunia is a distribution company for light steel under the Tasso brand. Distribution process in PD. Karunia uses the Microsoft Excel system, so it takes a long time to process sales receipts, it is difficult to see the history of purchases and sales of goods and it takes a long time to process the required reports. Therefore this study aims to provide solutions to problems that occur by using a distribution information system with the PHP programming language and MySQL database using the Laravel framework. So the author develops the system using the waterfall method and system modeling is designed using use case diagrams, activity diagrams, and class diagrams. This research can produce a system that can help distribute mild steel to facilitate PD. Karunia makes data processing better